Synthesis of nano-calcium carbonate from waste cement and techno-economic and environmental evaluation - Park, Kwangho; Lee, Kyung Rok; Jo, Hoyong; Park, Jinwon; Lee, Jay H.; Jung, Kwang-Deog (Elsevier BV, 2024)
Mineral carbonation stands out not only as an effective method for reducing CO2 emissions but also as a strategic approach to upcycling industrial waste. This study introduces a novel procedure for generating high-purity nano-calcium carbonate (nCaCO(3)) from waste cement powder, deploying hydrochloric acid (HCl), and sodium hydroxide (NaOH), both obtained through the electrolysis of sodium chloride (NaCl). Our approach, aimed at both environmental preservation and techno-economic feasibility, encompasses optimizing calcium extraction conditions through rigorous analysis of variables such as HCl concentration, solid-to-liquid ratio, and reaction temperature, subsequently proposing a rate law for the extraction process. Furthermore, the method emphasizes the production of high-purity CaCO3 by meticulously removing metallic impurities from the extracted solution with 1.0 M NaOH, culminating in pure calcium hydroxide and the generation of nCaCO(3) particles with superior purity (>99 %) and a uniform particle size (80-140 nm). An exhaustive environmental and economic assessment indicates that our process, while consuming varying energy levels based on operational potentials, anticipates a significant reduction in CO2 emissions by 46.1 %, alongside a competitive production cost (335 USD/ton of nCaCO(3)), thereby demonstrating substantial advantages over traditional methods in terms of sustainability, efficiency, and cost-effectiveness.